PENGARUH UPAH MINIMUM REGIONAL (UMR) DAN TINGKAT PENDIDIKAN TERHADAP JUMLAH PENDUDUK MISKIN PROVINSI RIAU 2011-2022 - aswanto aswanto (JURNAL PUNDI, 2023)
ABSTRAK The problem of poverty is a problem that cannot be denied by every country. So that this poverty problem should be a concern to be resolved, in the sense that the number of poor people every year has decreased from year to year. Poverty is not only the responsibility of the central government and local governments, but it should also be a concern for the individual himself how to try as much as possible. Because poverty does not just appear but of course there are factors that cause it. Of course, of the many factors, in this study there are two things that can affect the number of poor people in Riau Province, namely the Regional Minimum Wage (UMR) and the level of education. The wage received by a worker is the side of income that a worker can receive, so that with this income a person is able to meet the needs of life and his family. This means that the greater the wages received, the lower the number of poor people in a region. Meanwhile, education is capital for human resources that can improve their abilities both formally and skills, making it easier to find work because it has a high competitive value and results in productivity at work which will be able to meet the needs of their families. This study aims to examine the effect of Regional Minimum Wage and education level on the number of poor people in Riau Province 2011-2022. This study was analyzed using descriptive statistical analysis and multiple regression analysis using the Eviews 10 application. The results of this study found that the Regional Minimum Wage has a positive and significant effect on the number of poor people in Riau Province 2011-2022. While the level of education has a negative and significant effect on the number of poor people in Riau Province 2011-2022.Keywords : Regional Minimum Wage, Education Level, Number of Poor People